Threats to the validity of eye-movement research in psychology - Orquin, Jacob L; Holmqvist, Kenneth (Behavior research methods, 2018)
Eyetracking research in psychology has grown exponentially over the past decades, as equipment has become cheaper and easier to use. The surge in eyetracking research has not, however, been equaled by a growth in methodological awareness, and practices that are best avoided have become commonplace. We describe nine threats to the validity of eyetracking research and provide, whenever possible, advice on how to avoid or mitigate these challenges. These threats concern both internal and external validity and relate to the design of eyetracking studies, to data preprocessing, to data analysis, and to the interpretation of eyetracking data.
Keywords: Reproducibility of Results; Software; software; pohyby očí; Behavioral Research; lidé; reprodukovatelnost výsledků; Research Design; měření pohybů očí; Eye Movements; Eye Movement Measurements; výzkumný projekt; behaviorální výzkum; Humans